Theoretical Aspects of Biodiversity Protection in European Monetary Legislation - Dimitrijević, Marko (Review of European and Comparative Law, 2025)
The subject of the analysis in the paper is an overview of the causes, features, and consequences of the tendency of „greening” the concept of modern monetary law and central bank legislation to preserve natural resources in the context of biodiversity and provide a contribution to the realization of sustainable and humane economic development. In this sense, the paper tries to indicate the potential contribution of „green monetary legislation” in controlling and solving environmental problems, where a special place is devoted to identifying the potential ecological dimension of the mandate of the (European) Central Bank as the supteme monetary institution of the EU. In the following text, attention is paid to the functional analysis of the arguments that can justify the inclusion of environmental risks in central bank legislation. In contrast, in the furter text, attention is paid to identifying the potential legal basis for biodiversity protection in the central bank mandate. Although at first glance, it may seem that monetary legislation has no direct connection with environmental law and policy, practice shows that there is a high degree of functional and content consistency between the goals of contemporary environmental and monetary policy, which only speaks in favor of the thesis of the ‘green lex monetae’. By applying the dogmatic, axiological, and comparative legal methods, the author aims to point out the biggest dilemmas and challenges in the central bank’s legal contribution to environmental concerns, identify certain solutions de lege lata, and possibly offer certain common recommendations de lege ferenda.